A multiscale X-ray phase-contrast tomography dataset of a whole human left lung - Xian, Rui; Walsh, Claire L.; Verleden, Stijn E.; Wagner, Willi Linus; Bellier, Alexandre; Marussi, Sebastian; Ackermann, Maximilian; Jonigk, Danny D.; Jacob, Joseph; Lee, Peter D.; Tafforeau, Paul (Scientific data, 2022)
Technological advancements in X-ray imaging using bright and coherent synchrotron sources now allows the decoupling of sample size and resolution while maintaining high sensitivity to the microstructures of soft, partially dehydrated tissues. The continuous developments in multiscale X-ray imaging resulted in hierarchical phase-contrast tomography, a comprehensive approach to address the challenge of organ-scale (up to tens of centimeters) soft tissue imaging with resolution and sensitivity down to the cellular level. Using this technique, we imaged ex vivo an entire human left lung at an isotropic voxel size of 25.08 μm along with local zooms down to 6.05-6.5 μm and 2.45-2.5 μm in voxel size. The high tissue contrast offered by the fourth-generation synchrotron source at the European Synchrotron Radiation Facility reveals the complex multiscale anatomical constitution of the human lung from the macroscopic (centimeter) down to the microscopic (micrometer) scale. The dataset provides comprehensive organ-scale 3D information of the secondary pulmonary lobules and delineates the microstructure of lung nodules with unprecedented detail.
Gesehen am 08.07.2022